Greed, impatience and exchange rate determination - Frank Bohn (University College Dublin, UCD School of Economics, 2006)
This paper offers a theoretical explanation for the determination of exchange rates under specific conditions which can/could be found in some OECD and newly industrialised countries. In an Obstfeld (1994) framework extended to incorporate government expropriation reneging on a fixed exchange rate promise unambiguously produces short term benefits, but long term losses. The choice of exchange rate regime depends on the combined effect of greediness (expropriation) and impatience (political instability), though not straightforwardly. In particular, similarly stable countries may choose different exchange rate regimes due to different levels of rent-seeking, for instance Mexico and Chile in the 1980s.
hdl:10197/1341
Keywords: E42; F41; H29; 330; exchange rate regime; monetary policy; fiscal policy; expropriation; political instability; political economy